Development of an Intelligent Mechatronic System for Optimizing Household Energy Consumption (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This paper presents the design and development of an intelligent mechatronic system aimed at optimizing household energy consumption. The growing demand for electricity and the need for sustainable energy use have increased interest in smart home technologies. The proposed system integrates sensors, a microcontroller, relay switches, and a Wi-Fi module to monitor and control electrical appliances in real time. It collects data on energy usage and applies programmed logic to reduce unnecessary power consumption by automatically turning off idle devices. Users can also monitor and manage their energy usage remotely through a mobile application. The system is designed to be low-cost, user-friendly, and easily expandable for larger residential setups. Experimental results show up to 25% reduction in electricity usage during peak hours. This solution offers a promising approach to energy efficiency and cost savings in domestic environments, making it highly applicable for modern smart homes seeking sustainable and intelligent energy management systems.